Menachem Kellner: Jewish universalism - Tirosh-Samuelson, Hava; Hughes, Aaron W. (Library of contemporary Jewish philosophers, 2015)
Preliminary Material -- Menachem Kellner: An Intellectual Portrait /James A. Diamond -- Heresy and the Nature of Faith in Medieval Jewish Philosophy /Menachem Kellner -- Maimonides on the Science of the Mishneh Torah: Provisional or Permanent? /Menachem Kellner -- Maimonides’ “True Religion”: For Jews or All Humanity? /Menachem Kellner -- We Are Not Alone /Menachem Kellner -- Interview with Menachem Kellner /Hava Tirosh-Samuelson -- Select Bibliography.